Dictating High‐Capacity Lithium–Sulfur Batteries through Redox‐Mediated Lithium Sulfide Growth (Small Methods 6/2020). Issue 6 (9th June 2020) - Zhao, Meng; Peng, Hong‐Jie; Wei, Jun‐Yu; Huang, Jia‐Qi; Li, Bo‐Quan; Yuan, Hong; Zhang, Qiang
Abstract : Regulating the redox reactions is critical for rechargeable batteries based on conversion chemistries. In article number 1900344, Jia‐Qi Huang and co‐workers introduce cobaltocene as a persistent extrinsic redox mediator to dictate an alternative redox pathway, which not only benefits high‐rate or electrolyte‐lean lithium–sulfur batteries but also paves a way toward the rational design of novel redox mediators in dissolution‐precipitation energy chemistries.